Knowledge, Attitude and Self-efficacy towards Providing Sexual Counselling among Students Doing the Master of Counseling in Midwifery Program in Iran - Masoumeh Shayesteh; Razieh Lotfi; Effat Hatefnia; Mitra Rahimzadeh (Mashhad University of Medical Sciences, 2022)
Background & aim: Midwives play an essential role in sexual counseling. The present study aimed to measure knowledge, attitude and self-efficacy towards providing sexual counseling among students doing the master of Counseling in Midwifery program in Iran.Methods: This cross-sectional study was conducted on 148 midwifery students doing the master of Counseling in Midwifery, who selected via convenience sampling from universities across the country. Data collection was carried out using a researcher-made questionnaire including demographic characteristics, knowledge of sexual counseling (KSH), attitude towards sexual counseling (ASH), and self-efficacy to do sexual counseling (SESH) in 2021. Data analysis was done using the Student t-test, Pearson correlation test, and ANOVA using SPSS ver. 25.Results: Mean and standard deviation of the total score was 74.67 ±12 for knowledge, 80.8 ±76.98 for attitude, and 81 ± 16 for self-efficacy. Management of victims of sexual assault and counseling models had the lowest score on the knowledge scale. Students had poor self-efficacy when providing sexual counseling to the men and sexual minorities. There was a significant relationship between knowledge and attitude towards sexual counseling (P<0.001) A significant relationship was also seen between knowledge and attitude with self-efficacy of sexual counseling (p <0.001). Conclusion: Despite the optimal status of the overall sexual counseling knowledge, attitude, and self-efficacy scores, students still have low levels of competency in sexual counseling. It is necessary to improve the proficiency of students to communicate effectively with male clients, victims of rape, and sexual minorities through curriculum revision in terms of both theoretical and clinical issues.